2019
DOI: 10.1038/s41467-019-08352-5
|View full text |Cite
|
Sign up to set email alerts
|

PD-1/PD-L1 checkpoint blockade harnesses monocyte-derived macrophages to combat cognitive impairment in a tauopathy mouse model

Abstract: Alzheimer’s disease (AD) is a heterogeneous disorder with multiple etiologies. Harnessing the immune system by blocking the programmed cell death receptor (PD)-1 pathway in an amyloid beta mouse model was shown to evoke a sequence of immune responses that lead to disease modification. Here, blocking PD-L1, a PD-1 ligand, was found to have similar efficacy to that of PD-1 blocking in disease modification, in both animal models of AD and of tauopathy. Targeting PD-L1 in a tau-driven disease model resulted in inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
142
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(154 citation statements)
references
References 84 publications
(119 reference statements)
10
142
1
1
Order By: Relevance
“…Tregs are CD4 positive T-lymphocyte subsets that can maintain peripheral immune tolerance [25,46,47]. Previous and our studies have reported elevated Treg counts in AD patients and an Aβ-driven AD mouse model [17,27,48], supporting the notion that aging and AD are characterized by immune tolerance and/or immune senescence [13,49]. In the present study, the systemic reduction in peripheral Tregs after the IIV treatment was associated with the mitigation of the disease pathology and cognitive impairments.…”
Section: Discussionsupporting
confidence: 84%
“…Tregs are CD4 positive T-lymphocyte subsets that can maintain peripheral immune tolerance [25,46,47]. Previous and our studies have reported elevated Treg counts in AD patients and an Aβ-driven AD mouse model [17,27,48], supporting the notion that aging and AD are characterized by immune tolerance and/or immune senescence [13,49]. In the present study, the systemic reduction in peripheral Tregs after the IIV treatment was associated with the mitigation of the disease pathology and cognitive impairments.…”
Section: Discussionsupporting
confidence: 84%
“…With regard to the tauopathy study, Swartz and colleagues administered the same PD-1 antibody as in their Aβ model study to tauopathy mice at 8 months of age (a single intraperitoneal injection of 0.5 mg; Rosenzweig et al, 2019). The DM-hTAU mouse model has two tau mutations (K257T and P301S) and has impaired cognition and extensive tau pathology at this age (Rosenzweig et al, 2019). The single antibody injection improved cognition in a T-maze when examined 1 month later in a mixed-sex group.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the same group that showed beneficial effects of PD-1 blockade on Aβ clearance and cognition followed up on their pioneering findings demonstrating that similar benefits could be obtained in a tauopathy model using the same PD-1 antibody and isotype control as in their original study (Rosenzweig et al, 2019). Comparable results were observed with a PD-L1 antibody.…”
Section: Introductionmentioning
confidence: 90%
“…In summary, our findings have demonstrated a previously unrecognized role of neuronal PD-1 in regulating learning and memory. Previous studies showed that systemic anti-PD-1 treatment enhanced memory in mouse AD models, as a results of recruitment of immune cells (e.g., macrophages) and subsequent clearance of amyloid- plaques 3,4 . Contradictory results were also reported 5,6 .…”
Section: Pd1-deficient Neurons Showed No Changes In Ap Amplitude and mentioning
confidence: 99%